2011
DOI: 10.1111/j.1440-1754.2011.02015.x
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the number of street children and adolescents in two cities of Brazil using capture–recapture

Abstract: Children and adolescents on the streets are a common and underestimated occurrence in Maceió and Arapiraca. They have similar characteristics to street children from other countries and other cities in Brazil. The method of capture-recapture seems to be suited to study populations such as street children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
1
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 26 publications
1
10
1
2
Order By: Relevance
“…Likewise, results of the present study shows that 72.5% of the oncologists are male and more than half of total oncologists are hematologist-oncologists. On the other hand, a study shows that oncologists who have an academic position (32%) allocate little time to clinical services (20). Consistently, the present study found that on average about 31% of the oncologists have been working in academic settings.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Likewise, results of the present study shows that 72.5% of the oncologists are male and more than half of total oncologists are hematologist-oncologists. On the other hand, a study shows that oncologists who have an academic position (32%) allocate little time to clinical services (20). Consistently, the present study found that on average about 31% of the oncologists have been working in academic settings.…”
Section: Discussionsupporting
confidence: 76%
“…2017; 19 (7):e56126. 5 this study is that the overlaps from the 3 sources are small and the result attained may have an slight overestimation (20).…”
Section: Discussionmentioning
confidence: 99%
“…There were studies from 22 countries, the majority (62%) being from Africa [5,6,8,13,24–36] and South and Central America [10,1820,37–46], with the remainder located in Asia [9,4757], the Middle East [58,59] and Europe [60–64]. Almost all studies (41 of 50) were cross-sectional.…”
Section: Resultsmentioning
confidence: 99%
“…In the 1990s, “point-in-time” estimation [48] [69] and “plant/capture” correction procedures [70] were developed as advances over conventional homeless census techniques [71]–[73] and both were used in a number of US cities [47] [74] [75] (recently, see Bezerra et al [76]). Yet both point-in-time and plant/capture are dependent on the existence of total census operations for their effectiveness.…”
Section: Network Approaches To Homeless Population Estimationmentioning
confidence: 99%